Strategies for Organizing E-Voting-Based Village Head Elections in 2020: Study in Mempawah Regency, West Kalimantan Province - Andi Rizki Fathurrahman; Astika Ummy Athahirah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The e-voting-based village head election in Mempawah Regency experienced several obstacles in its implementation, including the lack of readiness of the Village Head Election Committee to supervise the implementation of activities and the limitations of e-voting tools. Besides that, the uneven socialization in the community resulted in many people not understanding the e-voting-based village head election procedures. This study aims to find the strategy for overcoming these problems. This study used a qualitative exploration method, collecting data through interviews and documentation. The results of data analysis show that the strategy is in quadrant I, namely the progressive strategy (S-O strategy), where strengths and opportunities have greater than weaknesses and threat